Sourcing strategies of U.S. service companies: a modified transaction-cost analysis - Murray, Janet Y.; Kotabe, Masaaki (Strategic Management Journal, 1999)
Global procurement of services has been receiving an increasing amount of managerial attention in recent years. Service firms seem to have begun sourcing part of their service activities from abroad in much the same way as manufacturing firms have sourced components and finished goods in the past 30 years. However, little is known about the nature of service sourcing strategy. In this study, we employ a modified transaction–cost analysis to examine empirically the locational (domestic vs. global sourcing) and the ownership (internal vs. external sourcing) aspects of service sourcing strategy. In addition, performance implications on both the locational and ownership aspects of service sourcing are investigated. The results show that, similar to components and finished goods procurement, supplementary services are sourced globally, either internally or externally. Furthermore, the relationship between asset specificity and internal sourcing of supplementary services is moderated by the level of inseparability and transaction frequency. Finally, internal sourcing and foreign sourcing of supplementary services are negatively related to a service’s market performance. Copyright © 1999 John Wiley & Sons, Ltd.